2 Answers | Add Yours
Since it is not specified what is the request of the problem, we'll simplify the given expression and we'll get:
We'll remove the brackets:
m+ n + 5m - 2
We'll re-arrange the terms and we'll combine like terms:
(m+5m) + (n-2)
The simplified expression is:
(m+n) + (5m-2) = 6m + n - 2
If the request of the problem was to determine m and n, we'll solve the problem:
(m+n) + (5m-2) = 0+0
We'll put the first bracket as 0:
m + n = 0 (1)
We'll put the second bracket as zero:
5m - 2 = 0
We'll add 2 both sides:
5m = 2
We'll divide by 5:
m = 5/2 (2)
We'll substitute m in (1):
5/2 + n = 0
We'll subtract 5/2 both sides:
n = -5/2
(m+n)+(5m-2) could be simpliflied.
Open the brackets:
=m+5m +n -2 , as n+m = m+n by commutative law.
=6m +n-2 , m+5m = 6m as like they are like terms.
Therefore (m+n) +(5m-2) = 6m+n-2.
We’ve answered 319,205 questions. We can answer yours, too.Ask a question